MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN 1 SAMPAI 5 BAGI ANAK TUNAGRAHITA SEDANG MELALUI MEDIA TIANG BILANGAN. - Elfi Rahmah; Markis Yunus; Fatmawati Fatmawati (Universitas Negeri Padang, 2013)
This research begins with the observation by the author in SLB Luki Padang, found that mental retardation children who do not know the numbers concept. From the observation of children have not been able to say, show and write the numbers 1-5 well. This research aim to prove that trough the medium of seguin better can improve recognition comprehend the numbers concept for mental retardation’s children in SLB Luki Padang. Research type is single subjet research (SSR) is a research method to see the trend graphs that compare the baseline condition (A) and treatment condition (B). Persuant to result of this research can mean that ability comprehend number concept to cihild with mental retardation of grade DIII/C in SLB Luki Padang mount through seguin bretter media.